Clinical Effect of Teucrium polium Extract Ointment on Post Pilonidal Sinus Excision Wound Healing: A Randomized Controlled Trial - Reza Hosseinpour; Nuruddin Hosseini; Seyedeh Fatemeh Hekmatzadeh; Saadat Mehrabi; Hossein Sadeghi Mansourkhani; Marita Mohamadshahi (Health Technology Assessment in Action)
Background: Due to the critical importance of post-surgical care for pilonidal sinus wounds, particularly in managing edema, infection, and related complications, it is essential to promote rapid wound healing. Objectives: This study aimed to evaluate the effect of Teucrium polium extract ointment as a wound repair agent for open pilonidal sinus surgery. Methods: This randomized double-blind clinical trial was conducted from April 2021 to March 2022. A total of 132 participants admitted to public hospitals in Yasuj with pilonidal sinus disease were randomized into three groups: T. polium ointment, serum, and placebo. The primary outcomes were changes in wound size and wound recovery time after surgery, while secondary outcomes included changes in wound edema and wound exudate. Results: The results indicated that the mean changes in wound size were statistically significant across all three groups over time (P <0.001). Between-group comparisons showed that from weeks 4 to 8, differences between the three groups were statistically significant (P< 0.001). Wound recovery time demonstrated a significant difference between the ointment and serum groups (P = 0.006) and between the ointment and placebo groups (P < 0.001). Wound edema and exudate improved over time for all three groups (P < 0.001), but follow-up results revealed a significant difference among the groups (P < 0.001). Conclusions: Based on the findings of this study and the comparison of the effects of T. polium ointment, it can be concluded that this ointment positively impacts wound healing following pilonidal sinus surgery, enhancing the healing process in both short-term and longterm care.